(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2018)
The research is devoted to definition of degree of food provision of the different-sized bream and roach groups, and to identification of their trophic relations in the northern part of the Caspian Sea. The water area of the Caspian Sea is broken into trade squares which have expansion on latitude of 10 miles and on the longitude of 7 miles. One nautical mile is equal to 1852 m. Each square is characterized by constant geographical coordinates and for convenience of use has constant number. When specifying the place of sampling in the operation used above the stated numbering of squares of the Caspian Sea. It begins in northern part of the sea and in the direction to the south numbers of squares increase. Low biomass of a benthos is characteristic of a considerable part of the water area of the Northern Caspian Sea. With increase in depth biomass of animals increases in the Northern Caspian Sea and reaches a maximum (to 100 g/m2) in the deep-water area at a depth of over 6 meters. Value of separate types of ground fauna in formation of the general efficiency of a bottom of the Caspian Sea isn not equivalent, therefore, studying of security with food of fish, can show not only a nourishness of hydrobionts but also fodder potential of sea pastures. Material for a research of feeding of a bream and a roach has been built during caspian filming, in autumn, 2016. In total 32 digestive tracts of fish, for studying of structure of food, from them the 12th intestinal path of breams and the 20th roach are analysed. It has been established that at breams from 21 squares the food bolus has been presented generally by chironomid larvae which have made 88,29% of mass of all food, and the nourishness index at the same time has made - 93,01%оо that is rather high rate. 3 breams from the 72nd square, with an average length of equal 212,4 mm., and average weight in 282,2gr, the food bolus supported Vermes, Crustacea, Mollusca, Foraminifera and detrit. At the 4th sample in intestines was only detrit, and one more individual had empty intestines. For comparison a roach from the same 72 square average length equaled 116 mm with an average weight 228, and in a food bolus - Vermes, Crustacea Mollusca also dominated, and Foramenifera, detritus contained, empty stomachs were not noticed. The roach filling index has made 72,05 %оо., and the bream from the same area the general index of filling of intestines, has made 40,13 %оо. Food of a roach from the square 263 was characterized by primary consumption of mollusks, and fish from squares 47, in a food bolus Vermes dominated, on the second place was Crustacea and on the third place was Mollusca, at the same time the index of filling was equal 57,10 %оо. It is established that the role of food organisms of a benthos in sagination of a bream and a roach in different areas of the sea is not identical. At the same time a variety of forms of ground fauna, and high plasticity in food of a bream and a roach provides a trophic optimum for existence of these species of fish in Northern the Caspian Sea.